PRONUNCIATION AND PHONETICS FOR YOUNG LEARNERS DEVELOPING LISTENING COMPREHENSION SKILLS - Anorboyeva Mahbuba; Maʼrufjonova Maftunaxon Nodirbek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article discusses effective activities for teaching minimal pairs or words that differ by only one sound essential for English as a Second Language (ESL) students aiming for pronunciation mastery. Recognizing and reproducing distinct sounds can be challenging for learners whose native languages do not differentiate these phonetic elements. By focusing on minimal pairs, these exercises not only improve pronunciation but also foster a dynamic learning environment where students can practice at their own pace while actively engaging with their peers.